2016
DOI: 10.17705/1cais.03839
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated User Satisfaction Model: Assessing Information Quality and System Quality as Second-Order Constructs in System Administration

Abstract: Abstract:While many studies have investigated the relationship between information systems (IS) characteristics and IS use, the results have been inconsistent. We argue that this inconsistency may be due to the modeling of information and system quality and the importance of the system usage context. We extend Wixom and Todd's (2005) integrated model of IS satisfaction by proposing and modeling information and system quality as second-order constructs and by testing the model in the system administration conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 64 publications
(126 reference statements)
2
19
0
1
Order By: Relevance
“…Therefore, we argue that customer review quality is another antecedent of social commerce trust. Our results are consistent with those of previous studies [29,101] and further our understanding of how to enhance consumers' social commerce trust and increase their e-commerce satisfaction. In addition, these results further clarify the mechanisms by which social commerce trust leads to ecommerce outcomes.…”
Section: Implications For Theorysupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, we argue that customer review quality is another antecedent of social commerce trust. Our results are consistent with those of previous studies [29,101] and further our understanding of how to enhance consumers' social commerce trust and increase their e-commerce satisfaction. In addition, these results further clarify the mechanisms by which social commerce trust leads to ecommerce outcomes.…”
Section: Implications For Theorysupporting
confidence: 92%
“…Social commerce trust thus occurs in a multi-dimensional context including people and technology dimensions. Accordingly, we model consumers' overall trust in social commerce as a second-order construct by capturing trust in different objects (e.g., trust in sites, trust in social media, trust in consumers) as first-order constructs [29]. Such studies are important to understand how different dimensions contribute to consumers' trust in e-commerce / social commerce overall.…”
Section: Definition Of Social Commerce Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive and highly significant path coefficient (β=.75, P <.001) supported the hypothesis that the more the patients’ initial expectations related to using a medical teleconsultation platform are confirmed, the better their perception of the quality of such a platform. The patients’ perceptions of the platform’s quality are deemed to be highly indicative of their affect level [ 50 ]. Hence, in line with expectation confirmation theory [ 18 ], we found that when confirmation of the patients’ initial expectations increases, so does their appreciation of the quality of mHealth IT and, in turn, their appreciation of their IT use experience.…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the concerns outlined in relation to systems and software's includes ineffective measurements, limited theoretical grounding, reliance on financial performance, lack of data collection, and limited knowledge on prediction (MARDIANA et al, 2015;MCLEAN, 2016). While many studies have investigated the relationship between information systems (IS) characteristics and IS use, the results have been inconsistent (FORSGREN et al, 2016). This severe mixed results and lack of empirical focus on systems outlines psychological, cognitive and passionate prospects which could intervene the relationship between the instruments and predictors of success (SNEAD, MAGAL, CHRISTENSEN; NDEDE-AMADI, 2015).…”
Section: Introductionmentioning
confidence: 99%